2008
DOI: 10.1089/jwh.2008.0798
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Residents' Perceived Ability to Direct Patient Care: Impact of Gender and Experience

Abstract: Background: Physicians are expected to effect patient care by giving orders to members of a healthcare team. Because women are socialized to be less directive than men, the assertive behavior required of new physicians may be experienced differently by male and female residents. We sought to explore the effects of gender and year of training on residents' experiences and perceived ability to direct patient care. Methods: This was a mixed-methods, cross-sectional, descriptive study employing a quantitative writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 20 publications
2
47
0
Order By: Relevance
“…Second, we found that women residents had more negative perceptions of the SUC for professionalism than men. These findings may be due to gender-based differences of empowerment and confidence consistent with prior research 19 50. More research is needed to confirm, better understand and remedy these differences.…”
Section: Discussionsupporting
confidence: 72%
“…Second, we found that women residents had more negative perceptions of the SUC for professionalism than men. These findings may be due to gender-based differences of empowerment and confidence consistent with prior research 19 50. More research is needed to confirm, better understand and remedy these differences.…”
Section: Discussionsupporting
confidence: 72%
“…This may represent inherent personality differences between surgeons and internists,54 or elements of surgical versus medical culture that were not captured by the safety culture metrics in our study 55 56. In addition, male gender was associated with speaking up in the professionalism vignette but not in the traditional vignette, perhaps due to the more confrontational nature of addressing unprofessional behaviour21 22 and previously reported gender-based differences in confidence and empowerment 8 57. Finally, site differences persisted even after controlling for various patient safety-related climates and respondent characteristics and may reflect elements of organisational culture not captured in our study or the influence of regional differences in assertive communication 58.…”
Section: Discussionmentioning
confidence: 73%
“…In female medical students, an association was found between high reticence scores and low assertiveness scores. 30 A study of internal medicine residents 32 showed that female residents reported more gender issues and chose lessassertive behaviors in clinical scenarios. Despite remarkable social changes in the last 25 years, there has been relatively little change in stereotypical gender behavior; men are still expected to be ''assertive,'' and women are expected to be ''compassionate'' and ''yielding.''…”
Section: Discussionmentioning
confidence: 99%
“…33 Although female residents may be in positions of authority and may direct their patients' care, they may avoid using assertive styles that lead to potential ''social penalties'' for nonconformation to stereotypical female roles. 32 As a group, residents most commonly utilized accommodating styles, followed by avoiding styles. The least preferred conflict style was collaborating, followed by competing.…”
Section: Discussionmentioning
confidence: 99%